Effects of Homelessness and Child Maltreatment on the Likelihood of Engaging in Property and Violent Crime During Adulthood. - Cronley, Courtney; Jeong, Seokjin; Davis, Jaya B.; Madden, Elissa (Journal of Human Behavior in the Social Environment, 2015)
The current study employs data from the U.S. National Longitudinal Study of Adolescent Health (N= 10,818; 56% female; 21% African American) to test how experiencing homelessness through emerging adulthood and child maltreatment predict adult property crime and violent crime. Unlike many published studies on homelessness, we used propensity score matching to correct for selection bias between homeless and nonhomeless individuals. Logistic regression models were run to predict violent and property crime in adulthood, controlling for child maltreatment. Participants who experienced homelessness by age 26 were 1.6 times more likely to commit violent crime in adulthood and almost 30% more likely to commit property crime. Those who were victims of child maltreatment were 15 times more likely to commit property crime, but no more likely to commit violent crime. Findings show that comparing statistically equivalent groups, homelessness through emerging adulthood significantly predicted adult criminality while child maltreatment showed more variable results. Greater prevention efforts aimed at children and adolescents at high risk of experiencing homelessness, as well as more intensive outreach services to homeless youth, may moderate exposure and reduce reliance on criminal survival behaviors.